Prophetic Leadership Study:Anarrative Review on Islamic Banking Institutions - Putra Salmon, Indra Pratama; Diana, Bambang Agus; Harta, Ridho; Yandes, Jufri (Jurnal Ilmiah Syi'ar, 2023)
Islamic banking organizations that show two sides of achievement targets, namely economic achievements and socio-religious mission achievements, also bring two consequences whether to bring the organization towards achieving material benefits or carrying out only socio-religious missions. In this context, organizational leaders have a strategic role in making Islamic banking institutions capable of optimally achieving their goals. This study aims to explain whether prophetic leadership is able to balance the current situation with beliefs that are conventional enough to be understood, and; see what variables are relevant to the prophetic leadership variable when applied to Islamic banking institutions. This article uses a phenomenon-based review of Islamic banking and its governance policies as the object of study. Narrative review of literature studies is the main approach in writing articles. The results of the study show that the issue of prophetic leadership has a pattern that is in accordance with the specificity of the locus of study (Islamic banking institutions), which then shows that the modern leadership that is widely presented in western literature is not the best. The relevance and superiority of prophetic leadership in the form of the role of maintaining the professionalism and morality aspects of performance so as to be able to balance economic activities with social activities in the midst of the rapid issue of banking capitalism in Indonesia. Through maqasid ash-shariah on the policies of Islamic banking institutions in Indonesia, prophetic leadership is able to go hand in hand with business processes and their application to Islamic banking. The implication of this study is to provide an understanding that prophetic leadership which has been implemented long before the emergence of western leadership models, is still very relevant in dealing with changing times and has the opportunity to become an alternative to leadership in the modern era like today.